2010
DOI: 10.1007/s11390-010-9398-x
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Set of Complexity Metrics for Large-Scale Object-Oriented Software Systems

Abstract: Ma YT, He KQ, Li B et al. A hybrid set of complexity metrics for large-scale object-oriented software systems. AbstractLarge-scale object-oriented (OO) software systems have recently been found to share global network characteristics such as small world and scale free, which go beyond the scope of traditional software measurement and assessment methodologies. To measure the complexity at various levels of granularity, namely graph, class (and object) and source code, we propose a hierarchical set of metrics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…This can reduce trustworthiness of the proposed metrics. It is worth noticing that only three of the proposed studies are validated independently ( [22,46,45]). Independent validation (not performed by the metrics' main proponents) is very important for the proof of metrics usefulness before common acceptance is sought.…”
Section: Modulementioning
confidence: 99%
See 1 more Smart Citation
“…This can reduce trustworthiness of the proposed metrics. It is worth noticing that only three of the proposed studies are validated independently ( [22,46,45]). Independent validation (not performed by the metrics' main proponents) is very important for the proof of metrics usefulness before common acceptance is sought.…”
Section: Modulementioning
confidence: 99%
“…et al [13] Graph-based Maintainability, Bug severity MD=2, MQ=1, LV=3, USB=2, CA=1, AP=3, TS=2 Elish [22] Internal structure Understandability MD=-, MQ=1, LV=4, USB=3, CA=1, AP=2, TS=2 Gupta et al [27] Internal structure Understandability MD=3, MQ=1, LV=2, USB=2, CA=1, AP=2, TS=2 Gupta et al [28] Internal structure Reusability MD=3, MQ=3, LV=1, USB=2, CA=2, AP=2, TS=2 Haohua et al [29] Graph-based Complexity MD=2, MQ=1, LV=3, USB=2, CA=1, AP=2, TS=2 Hu et al [30] Specific model Maintainability MD=2, MQ=2, LV=2, USB=2, CA=1, AP=2, TS=1 Hwa et al [31] Internal structure Understandability MD=2, MQ=3, LV=2, USB=2, CA=1, AP=2, TS=2 Kanjilal et al [32] Graph-based Complexity MD=2, MQ=1, LV=2, USB=3, CA=1, AP=2, TS=1 Lindvall et al [44] Internal structure Maintainability MD=1, MQ=3, LV=2, USB=2, CA=1, AP=3, TS=2 Ma et al [45,46] Graph-based Complexity, Fault rate MD=-, MQ=1, LV=4, USB=2, CA=2, AP=2, TS=2 Misic [47] Internal structure External coherence MD=3, MQ=1, LV=1, USB=3, CA=1, AP=2, TS=1 Reddy et al [52] Graph-based Complexity MD=2, MQ=3, LV=1, USB=2, CA=2, AP=2, TS=1 Salman [54] Internal structure Maintainability, Integrability MD=3, MQ=1, LV=3, USB=3, CA=1, AP=2, TS=1 Sarkar et al [57] Internal structure Modularization MD=2, MQ=1, LV=3, USB=2, CA=1, AP=2, TS=2 Sartipi [58] Graph-based Modularization MD=2, MQ=1, LV=2, USB=2, CA=1, AP=3, TS=2 Sheresh. et al [60] Specific model -MD=2, MQ=2, LV=-, USB=1, CA=1, AP=1, TS=1 Wei et al [61] Graph-based -MD=2, MQ=1, LV=-, USB=2, CA=1, AP=1, TS=1 Yu et al [62] Specific model Fault rate MD=1, MQ=1, LV=2, USB=2, CA=1, AP=2, TS=2 Zhou et al [63] Graph-based External coherence MD=3, MQ=1, LV=2, USB=2, CA=2, AP=2, TS=2…”
Section: Referencementioning
confidence: 99%
“…Jiang [4] found that source code metrics perform better than design level metrics and combination of them performs the best. Y Ma [5] proposed a hybrid set of complexity metrics for large scale object oriented systems. Authors [6] suggested new software metrics based on coding standards violations to capture latent faults in a development.…”
Section: Related Workmentioning
confidence: 99%
“…Lanza and Marinescu [11] introduces detection strategies for disharmonies with software design metrics. Yu-Tao [12] mixes metric based and graph based approaches to help finding error prone classes, treating complex software systems as large networks.…”
Section: Related Workmentioning
confidence: 99%